False Coronavirus Disease 2019 Cases due to Contamination by Inactivated Virus Vaccine. (9th September 2021) - To, Kelvin Kai-Wang; Li, Xin; Lung, David Christopher; Ip, Jonathan Daniel; Chan, Wan-Mui; Chu, Allen Wing-Ho; Yip, Cyril Chik-Yan; Chen, Jonathan H K; Poon, Rosana Wing-Shan; Tsoi, Hoi-Wah; Lai, Raymond Wai-Man; To, Wing-Kin; et al.
Abstract: A false-positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse-transcription polymerase chain reaction result can lead to unnecessary public health measures. We report 2 individuals whose respiratory specimens were contaminated by an inactivated SARS-CoV-2 vaccine strain (CoronaVac), likely at vaccination premises. Incidentally, whole genome sequencing of CoronaVac showed adaptive deletions on the spike protein, which do not result in observable changes of antigenicity.